PROSPECTS AND RISKS OF ARTIFICIAL INTELLIGENCE IN MEDICINE AND MEDICAL EDUCATION - Dr. Imran Aslam Ph.D.; Dr. Muhammad Kalim Raza; Dr. Ayesha Ashraf; Dr. Vishal Chauhan (Journals Park Publishing, 2025)
Artificial Intelligence (AI) is transforming medicine and medical education by providing novel opportunities to enhance clinical outcomes, improve diagnostic tools, and refine instructional methodologies. Nonetheless, its swift incorporation presents considerable ethical, legal, and practical issues. This study investigates the advantageous applications and possible hazards of AI in healthcare, concentrating on its function in clinical practice, patient care, and medical education. It offers a comprehensive perspective on AI's present and future influence in the medical domain, emphasizing avenues for advancement and approaches to alleviate associated concerns. The results underscore the necessity for prudent AI deployment and continuous investigation to tackle related issues.
Keywords: Artificial Intelligence, Healthcare, Medical Education, Machine Learning, Diagnostic Tools, Ethical Issues, Algorithmic Bias, Virtual Simulations.